Keefektifan Metode Pembelajaran Talking Stick Untuk Meningkatkan Semangat belajar Siswa dalam Pembelajaran PPKn - Icha Amelia; Anjeli Harpina Purba; Reh Bungana Br. Perangin-Angin (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
The main purpose of this research is to produce interesting learning methods in Pancasila and Citizenship Education subjects that can increase students' enthusiasm for learning, then to determine student learning outcomes using the talking stick learning method and how students respond to the talking stick learning method. This research is a descriptive quantitative research conducted in the even semester of the 2021/2022 academic year, which is located at SMP Negeri 35 Medan. The sample is class VIII B SMP Negeri 35 Medan. The sampling technique used is saturated sampling, that is, all of the population is sampled. The results of this research is that the students of class VIII B SMP Negeri 35 Medan are very enthusiastic about the talking stick learning method in civics learning. Students feel happy with the talking stick learning method than can eliminate drowsiness and boredom when learning civics, increase curiosity about civics learning materials, and the instructions given can be easily understood by students. So that the talking stick learning method is effective to be applied in the civics learning proses to increase students' enthusiasm for learning